Collaborative Governance dalam Pengembangan Desa Wisata Kemetul, Kecamatan Susukan, Kabupaten Semarang - Aninda Diah Maharani Utami; , Dyah Hariani; Susi Sulandari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
Desa Wisata Kemetul has been running for about 10 years, but its development is slow and its existence is not widely known by the public, which is the background of this research. Lack of commitment from stakeholders so that the development of this tourist village is not running optimally. Based on this, the researchers conducted research related to collaborative governance and the success factors in the development of the Desa Wisata Kemetul. The purpose of this study was to determine the analysis of collaborative governance and the factors that support its success in the development of the Desa Wisata Kemetul. The research method used in this research is descriptive qualitative. The main research subjects are stakeholders related to purposive sampling technique. The research site is in Desa Wisata Kemetul with data collection techniques through direct observation, interviews, related documents and audio-visual materials. The results of the study show thatfaces collaborative governance stillmany obstacles, this is evidenced by the analysis ofmodel collaborative governance Ansell and Gash's, such as: strictness of rules, understanding of shared vision and mission, lack of commitment and participation. The supporting success factors are: strong trust, the existence of regulations, the division of responsibilities, the sharing of information and the availability of resources, besides that there are several indicators that have not been met, namely: network structure, commitment and clarity of governance.